The Role of Criminalistics in The Solution of Crime - Yangiboyev Abdugaffor Davlat o’g’li; Ergashev Elbek Elyor o’g’li; Karimov Behzodjon Asqarjon o’g’li; Ortiqov Nodirbek Elmurod o’g’li (Scientific Trends, 2025)
This article provides information about the role of forensic science in solving crimes. It focuses on the study of scientific methods, tools and methods for the detection, detection, investigation and prevention of crimes. On the basis of current modern methods, the prospects for the development of the science of criminalistics are highlighted.
Keywords: Law, constitution, crime, criminology, expertise, Forensic biological expertise, dactyloscopic expertise, ballistic expertise, trasological expertise, identification, search, object, subject, scene, material evidence, legal significance.